New religious movements in the twenty-first century: legal, political, and social challenges in global perspective - Lucas, Phillip Charles; Robbins, Thomas (Routledge, 2004)
Introduction. Alternative religions, the state, and the globe / Thomas Robbins -- pt. 1. Western Europe. General overview of the "cult scene" in Great Britain / Eileen Barker -- Religious minorities and new religious movements in Denmark / Armin W. Geertz and Mikael Rothstein -- France's obsession with the "sectarian threat" / Danièle Hervieu-Léger -- The secte response to religious discrimination : subversives, martyrs, or freedom fighters in the French sect wars? / Susan J. Palmer -- Italy's surprisingly favorable environment for religious minorities / Massimo Introvigne -- New religions in Germany : the publicity of the public square / Brigitte Schoen -- pt. 2. Eastern Europe and Eurasia. New religions in the new Russia / Marat Shterin -- New religious minorities in the Baltic States / Solveiga Krumina-Konkova -- Crushing Wahhabi fundamentalists in Central Asia and the Caucasus : subplot to the global struggle against Al Qa'ida or suppression of legitimate religious opposition? / Brian Glyn Williams -- pt. 3. Africa, Asia, and Australia. Prophets, "false prophets," and the African state : emergent issues of religious freedom and conflict / Rosalind I.J. Hackett -- Religion on a leash : NRMs and the limits of Chinese freedom / Scott Lowe -- Consensus shattered : Japanese paradigm shift and moral panic in the post-Aum era / Ian Reader -- New religions in Australia : public menace or societal salvation? / James T. Richardson --